Peran Perpustakaan Perguruan Tinggi dalam Lingkup Komunikasi Ilmiah - Aldi Rahman Untoro; Taryono Taryono (Pustakaloka, 2022)
Scholarly communication occurs fundamentally in college environment. Aim research is knowing how to role of library in scholarly communication which happened in college environment. This research using descriptive methods with qualitative approach, data collection with documentation technique. Libraries are expected gain further role about scholarly communication. This research intended for academic libraries, to be more understanding about their perspective role in scholarly communication.